2012
DOI: 10.1016/j.beth.2012.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Cognitive Behavioral Training Within Doctoral Psychology Programs in the United States: Report of the Inter-Organizational Task Force on Cognitive and Behavioral Psychology Doctoral Education

Abstract: The Association for Behavioral and Cognitive Therapies initiated an interorganizational task force to develop guidelines for integrated education and training in cognitive and behavioral psychology at the doctoral level in the United States. Fifteen task force members representing 16 professional associations participated in a year-long series of conferences, and developed a consensus on optimal doctoral education and training in cognitive and behavioral psychology. The recommendations assume solid foundationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 4 publications
1
60
0
4
Order By: Relevance
“…The use of virtual reality for the clinical assessment and treatment of psychosis is still in its infancy, but the first clinical trials have been published or are ongoing. In these studies participants either practice new social skills 5 , or are encouraged to drop their safety behaviours and explore new ways of approaching social situations 6,7 or challenge the omnipotence of the voices they hear 8 . The initial results indicate that virtual reality assisted therapy can be a powerful tool to help people break the cycle of avoidance involved in the maintenance of symptoms and develop new skills and strategies to cope with them.…”
Section: The Use Of Virtual Reality In Psychosis Research and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of virtual reality for the clinical assessment and treatment of psychosis is still in its infancy, but the first clinical trials have been published or are ongoing. In these studies participants either practice new social skills 5 , or are encouraged to drop their safety behaviours and explore new ways of approaching social situations 6,7 or challenge the omnipotence of the voices they hear 8 . The initial results indicate that virtual reality assisted therapy can be a powerful tool to help people break the cycle of avoidance involved in the maintenance of symptoms and develop new skills and strategies to cope with them.…”
Section: The Use Of Virtual Reality In Psychosis Research and Treatmentmentioning
confidence: 99%
“…Science requires pre-analytic assumptions about the nature of data, truth, and the questions of importance, and some of the differences between the waves and generations of CBT work were philosophical, not empirical. Recognizing this, the Inter-Organizational Task Force on Cognitive and Behavioral Psychology Doctoral Education 8 recently concluded that all CBT training should place more emphasis on philosophy of science training, in the hope of increasing the coherence and progressivity of research programs. An examination of assumptions leads naturally to a concern for theories, models, and processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The well-documented need to educate clinicians in best practices has led to the encouragement of graduate schools to provide ample opportunity for novice therapists to learn CBT-ERP during their initial graduate training (Klepac et al, 2012). In support of this recommendation, empirically supported training models for CBT-ERP that emphasize exposure therapy need to be developed so that they can be adopted by training sites.…”
Section: Introductionmentioning
confidence: 90%
“…The various treatments within the broad family of CBTs , each emphasize somewhat different processes Hofmann 2017, 2018;Klepac et al 2012), and there are suggestions of processes that can occur in the absence of cognition (Mennin et al 2013, and see review in;Lorenzo-Luaces et al 2015). The past two decades have witnessed some further advances, whereby core dimensions in psychopathology have been linked to treatment processes that are broadly relevant to the typical case presentation in the consultation office; where either full or partial DSM criteria for multiple disorders are met.…”
Section: Treatment Processesmentioning
confidence: 99%